The intellectual capital performance of banking sector in Pakistan - Kamath G. Bharathi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Efficiency in using of resources plays an important role in determining the strength of the organization. Efficiency measured purely on financial variables does not give the true picture especially in sectors which are intellectual capital intensive. The present paper is an attempt to measure the performance of banks in Pakistan on a new dimension of intellectual capital. This paper estimates the value added intellectual capital (VAIC) of the banks in Pakistan for a 2 year period. The study concludes that the private sector banks were doing much better than all other banks in Pakistan on intellectual capital efficiency levels. The good performance is attributed to efficient usage and management of human resources.
Keywords: 330; human capital; structural capital; banking sector; Pakistan